Preacinetobactin not acinetobactin is essential for iron uptake by the BauA transporter of the pathogen Acinetobacter baumannii - Moynié, L; Serra, I; Scorciapino, MA; Oueis, E; Page, MG; Ceccarelli, M; Naismith, JH (eLife Sciences, 2018)
New strategies are urgently required to develop antibiotics. The siderophore uptake system has attracted considerable attention, but rational design of siderophore antibiotic conjugates requires knowledge of recognition by the cognate outer-membrane transporter. Acinetobacter baumannii is a serious pathogen, which utilizes (pre)acinetobactin to scavenge iron from the host. We report the structure of the (pre)acinetobactin transporter BauA bound to the siderophore, identifying the structural determinants of recognition. Detailed biophysical analysis confirms that BauA recognises preacinetobactin. We show that acinetobactin is not recognised by the protein, thus preacinetobactin is essential for iron uptake. The structure shows and NMR confirms that under physiological conditions, a molecule of acinetobactin will bind to two free coordination sites on the iron preacinetobactin complex. The ability to recognise a heterotrimeric iron-preacinetobactin-acinetobactin complex may rationalize contradictory reports in the literature. These results open new avenues for the design of novel antibiotic conjugates (trojan horse) antibiotics.